Association between ambient air pollution and dry eye symptoms among Chinese individuals during the COVID-19 pandemic: a national-based study - Kai, Jia-Yan (2024)
Purpose: To examine the association between ambient air pollution and dry eye symptoms (DES) during the COVID-19 pandemic and explore whether air pollution had increased the risk of DES to a greater extent than other risk factors. Methods: A nationwide cross-sectional survey was conducted from June 20, 2022 to August 31, 2022. The Ocular Surface Disease Index-6 (OSDI-6) questionnaire was used to assess the presence of DES. Logistic regression models were employed to analyze the associations between DES and air pollution variables, including air quality index (AQI), fine particulate matter (PM2.5), PM10, sulfur dioxide (SO2), carbon monoxide (CO), nitrogen dioxide (NO2), ozone (O3) and residing near industrial zones. We explored the interactions of air pollutants and other risk factors in the additive models by calculating the synergy index (SI). Standardized regression coefficients were calculated to compare the relative importance of risk factors for DES. Results: A total of 21,909 participants were included in the analysis. Residing near industrial zones was significantly correlated with a higher risk of DES (Odds ratio (OR): 1.57, 95 % confidence interval (CI): 1.38–1.79). No significant associations were found between DES and air pollutants except SO2 (OR: 1.05, 95 % CI: 1.02–1.09, per standard deviation increment in SO2 concentration). The restricted cubic spline analyses revealed a linear concentration-response relationship between SO2 and DES. The interaction analyses suggested synergetic interactions of SO2 with depression and problematic internet use. Among the risk factors, depression, anxiety, and problematic Internet use contributed more to the increased risk of DES. Conclusion: The association between ambient air pollutants and DES may have been mitigated during the pandemic due to increased time spent indoors. Despite this, our findings support the deleterious health impact of air pollutants. Future urban planning should plan industrial zones further away from residential areas.